Social economy and state aids - Piernas López, Juan Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This contribution aims to analyse how the State aid discipline, in particular the notion of State aid under Article 107(1) TFEU, the rules on compatibility of aid under Articles 107(2) and 107(3) TFEU and those on services of general economic interest under Article 106(2) TFEU, allow for the granting of financial support to social economy actors. The article draws in particular on the changes in primary law brought about by the Treaty of Lisbon, the case law of the EU courts and the decision-making practice of the European Commission. Finally, several concluding remarks are included
Keywords: Social economy; state aid; definition; compatibility; SGEI